Conceptual Design of Electrical Ducted Fan (EDF) - Junaidin, Buyung; Cahyono, M. Ardi (Sekolah Tinggi Teknologi Adisutjipto, 2019)
Electric Ducted Fan (EDF) is an electric propulsion consist of duct, fan and electric motor with main power source is from battery which generates compression air for thrust. EDF is used as an alternative propulsion for high speed UAV especially for target UAV or ?bomb? controlled UAV. It?s design is very simple and no need extra maintenance compared to jet engine. Design process of an EDF is more simple than a jet engine, nevertheless it could obtain enough thrust for high speed flying. The aim of this research is to design an EDF as an alternative propulsion for high speed UAV and performance analyzing of EDF using analitical approach. Design of EDF produce an EDF with inlet and outlet diameter are 70mm and 60mm. Total length of EDF is 116,1mm. Performance analysis of EDF shows that by 700W of motor power could reach 16N of thrust which is accepted performace for 70mm EDF.